Reducing the complexity of LDPC decoding algorithms: An optimization-oriented approach - Sarajlic, Muris; Liang Liu; Edfors, Ove (IEEE International Symposium on Personal, Indoor, and Mobile Radio Communications workshops (Print), 2014)
This paper presents a structured optimization framework for reducing the computational complexity of LDPC decoders. Subject to specified performance constraints and adaptive to environment conditions, the proposed framework leverages the adjustable performance-complexity tradeoffs of the decoder to deliver satisfying performance with minimum computational complexity. More specifically, two constraint scenarios are studied: the "good-enough" performance and "as-good-as-possible performance". Moreover, we also investigate the effects of different degrees of freedom in performance-complexity tradeoff adjustments. The effectiveness of the proposed method has been verified by simulating a set of LDPC codes used in IEEE 802.11 and IEEE 802.16 standards. Computational complexity reductions of up to 35% have been observed.